Senescence caused by inactivation of the homeodomain transcription factor Pdx1 in adult pancreatic acinar cells in mice. Issue 16 (30th June 2019) - Horiguchi, Masashi; Yoshida, Masahiro; Hirata, Koji; Furuyama, Kenichiro; Masui, Toshihiko; Uemoto, Shinji; Kawaguchi, Yoshiya
Abstract : In this study, we used tamoxifen‐inducible Elastase‐Cre–mediated inactivation of pancreatic and duodenal homeobox1 (Pdx1), an indispensable gene during embryonic pancreatogenesis, to investigate the role of Pdx1 in adult pancreatic exocrine tissue. We found that Pdx1 depletion in approximately 50% of acinar cell mass did not show any macroscopic phenotype. Lineage tracing experiments revealed that the percentage of Pdx1‐depleted cells did not change initially but gradually decreased, while the proliferation of Pdx1‐preserved cells increased. Electron microscopic analysis showed the emergence of round‐shaped mitochondria with less cristae, dilated ER lumen and increased number of autophagosomes but no apoptosis. Instead, Pdx1‐depleted acinar cells became senescent. These findings indicate that intracellular stress caused by Pdx1 inactivation triggers the senescence‐associated secretory phenotype to maintain organ homeostasis in this model. Abstract :